A Case of Type I Sirenomelia Complicated by Severe Oligohydramnios in the First Trimester - Atsushi Yoshida; Asumi Okumura; Masahiro Nakao; Ryo Suzuki (Hindawi Limited, 2019)
Sirenomelia is a very rare congenital anomaly. Type I is the mildest type, and the long bone structures are all normally present with only soft tissue fusion. We experienced a case of type I sirenomelia complicated by severe oligohydramnios. Because of severe oligohydramnios, ultrasonographic images were not very clear. The associated findings with sirenomelia (single umbilical artery and bilateral renal agenesis) were helpful for the prenatal diagnosis of this disease. Detailed sonographic examination of the fetus was thought to be necessary for the accurate prenatal diagnosis of sirenomelia.